The impact of actions coordinated by a multidisciplinary team on adherence to outpatient cardiac treatment - Sturzeneker , Mário Cláudio Soares; Dlugosz , Ana Carla; Parlow , Jaqueline Meert; Sakakibara , Amy; Fonseca , Mariana; Koscianski , Alice Magro; Baroni, Gilberto; Mansani, Fabiana Postiglione (Seven Editora, 2023)
Introduction: The therapeutic decision must be an active process between the health team and the patient. The benefits of treatment adherence are widely known, however, adherence is a challenge that has been described since 1970. Such a scenario reflects the increase in morbidity and mortality from cardiac conditions. The present study is based on actions coordinated by a multidisciplinary team, consisting of members of the pharmacy, social assistance, and cardiology services, aiming to identify and resolve the factors that may influence adherence to outpatient cardiac medical treatment and to evaluate the impact of these actions in this process. Methods: Longitudinal study that included 15 patients treated at the cardiology outpatient clinic of the Hospital Regional dos Campos Gerais, carried out from May to December 2022. At first, the patients were seen in the conventional cardiology consultation and, later, they were directed to the multidisciplinary consultation. The study evaluated sociodemographic and clinical variables and analyzed lifestyle, quality of life, and adherence to therapy using validated questionnaires. After a period, which varied from 5 to 7 months, the patients were reassessed and submitted again to the questionnaires. Results: After the multidisciplinary intervention, there was an improvement, mainly, in the parameters of adherence to pharmacological therapy, a reduction in the number of sedentary individuals, an increase in quality of life, and less nicotine dependence among smokers. There was no change in the profiles related to smoking and alcoholism and little change associated with changing the therapeutic regimen (number of medications used daily). Conclusion: The multidisciplinary approach in the cardiological context promotes improvement in patients’ therapeutic adherence and lifestyle parameters, thus positively impacting the quality of life of patients with heart disease. DOI:https://doi.org/10.56238/alookdevelopv1-109